Anterior Chamber Epithelial Cyst After Uneventful Deep Anterior Lamellar Keratoplasty. Issue 10 (October 2016) - Costa, José F.; Rego, Marco; Rosa, Andreia; Costa, Esmeralda; Fonseca, Pedro; Cachulo, Maria Luz; Veríssimo, Júlia; Quadrado, Maria João; Murta, Joaquim
Abstract : Purpose: To report the case of an anterior chamber epithelial cyst after uncomplicated deep anterior lamellar keratoplasty (DALK) treated with a tissue-sparing surgical technique. Methods: A 35-year-old female patient underwent DALK in her OS because of stage IV keratoconus. The surgery was uneventful, and 3 months postoperatively, best-corrected visual acuity (BCVA) was 20/25. By the sixth postoperative month, a cystic iris lesion was noticed. The lesion grew progressively larger, and BCVA dropped to 20/63 in OS. Cyst excision was performed. Results: No complications possibly related to the surgery were observed. Two years later, BCVA was 20/25 in OS, and there were no signs of cyst recurrence. Histopathological examination of the lesion showed an epithelial implantation cyst. Conclusions: An anterior chamber epithelial cyst is a sight-threatening condition that may occur after DALK. In selected cases, a conservative surgical approach is an effective treatment option, conveying excellent functional and anatomical outcomes.